El conocimiento científico y tecnológico disponible en el departamento de Antioquia. 1990-2010 (2012)
ABSTRACT: The majority of indicating on science, technology and innovation are concentrate, like in the majority of international indicators, measuring the investment in ACTI (Activities of Science, Technology and Innovation), the intensity and amount of bibliographical production, or the production of patents, but no of these indicators measures the knowledge available.